International Experiences in Organizing Modern Primary Education Systems - Tojimirzayeva , Buzulaykho (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This thesis examines the issues of improving primary education systems based on modern international experiences. The key pedagogical principles of primary education systems in Singapore, Finland, and the United Kingdom are analyzed, and recommendations for their implementation in Uzbekistan’s context are developed. The study emphasizes issues such as student-centered approaches, interdisciplinary integrated curricula, updating the assessment system, teacher professional development, and fostering creative and practical activities. Additionally, a SWOT analysis of Uzbekistan’s primary education system based on international experiences is conducted.